THE BEST CRITERIA OF COPULA FOR MODELING DEPENDENCY ACROSS THE EXCHANGE RATE OF FOREIGN CURRENCY - IVALEN , HISTA
An in ation and de ation in the value of a country's currency can aect the value of other currencies. In this thesis the dependence will be seen between this exchange rate of foreign currencies, whether linear or not and how the structure of depen- dence. A tool that is usually used for modelling the dependence between two or more random variables is through its joint distribution function. If the value of de- pendence between random variables is zero, then its joint distribution function can be written as multiplication of its marginal distribution functions. And if the value of dependence is not zero then it is become a complex matter as there is no explicit form of its joint distribution function. For that, we need a method to overcome this problem, that called Copula. Copula is an 'extension' method in modelling de- pendency between random variables through distribution functions. In this thesis, author will find out the best Copula for modelling the dependence of the exchange rate from a few foreign currency using the data that already owned.